Improvement of the writing skill in students of the 2nd level of english at cec through an interactive digital application - Jaramillo Martínez, Maria Del Cisne; Plaza Minuche, Axel Santiago (Machala, Utmachala, 2022)
The main purpose of this research work is to improve the writing skills of second-level English students at the Centro de Education Continua through a digital application during August, based on the use of a system of didactic activities supported by an interactive digital tool, in response to the high degree of communicative difficulties in elementary-level students, during the virtual classes in 2022. This investigation is focused on the self-taught learning process involving 17-year-old students, in the same way, its bases are supported by the qualitative paradigm of a non-experimental nature of a single group. Includes a series of theoretical and empirical methods, both of which are tools to facilitate the processing and obtaining of information. Consequently, this investigative work represents a contribution to the area of foreign languages, aiming to innovate the daily learning tools of practice during and after classes in writing skill.
El presente trabajo investigativo tiene como propósito principal el mejoramiento de la habilidad writing en los alumnos de segundo nivel de Inglés del Centro de Educación Continua a través de una aplicación digital en el transcurso del mes de agosto, mediante el empleo de un sistema de actividades didácticas apoyadas en una herramienta digital interactiva, como respuesta al alto grado de dificultades de carácter comunicativo en alumnos de niveles elementario, que ha tenido lugar durante las clases virtuales del año 2022. La investigación tiene como objeto de estudio el proceso de aprendizaje autodidacta en estudiantes que comprenden un rango superior a los 17 años, asimismo sus bases se encuentran sustentadas en el paradigma cualitativo de naturaleza no-experimental de un solo grupo. Comprende una serie métodos teóricos y métodos empíricos, los cuales son instrumentos facilitares para el procesamiento y obtención de información. Por consiguiente, este trabajo investigativo representa un aporte del área de lenguas extranjeras, en el sentido de innovar las herramientas de aprendizaje diarias de práctica durante y posterior a clases en la habilidad de escritura.
Keywords: DIGITAL PLATFORM; CONNECTIVITY THEORY; SYSTEM OF DIDACTIC ACTIVITY; ENGLISH AS A FOREIGN LANGUAGE; TEACHING-LEARNING PROCESS